2014
DOI: 10.5455/aim.2014.22.133-138
|View full text |Cite
|
Sign up to set email alerts
|

A Roadmap to Pre-Implementation of Electronic Health Record: the Key Step to Success

Abstract: Introduction:Initial attempts are made to implement electronic health record (EHR) in Iran, the present study aim is developing a proper roadmap to EHR in pre-implementation phase by expert views on the matter.Method:An initial framework was developed for preimplementation based on reviewing literature on EHR implementation and descriptive-comparative with qualitative approaches in five countries. A questionnaire was designed in several sections using 47 main topics associated with pre-implementation. Cronbach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 14 publications
(19 reference statements)
1
41
0
5
Order By: Relevance
“…The selection of the project team is a vital contributing factor towards successful EHRS implementation (Adler, 2007;Carayon et al, 2009;Lorenzi et al, 2009). While some research has suggested that the formulation of an EHRS implementation project team should be the first step in the process of implementation (Adler, 2005;Sanchez et al, 2005), others have argued that the decision regarding composition of the project team is a step which should be taken only once the EHRS implementation plan has been approved (Ghazisaeidi et al, 2014). The project team are responsible for formulating a project plan, therefore the project team should be established early to ensure that all team members are involved in the early stage processes such as planning and decision-making.…”
Section: Factors Related To the Organisationmentioning
confidence: 99%
See 4 more Smart Citations
“…The selection of the project team is a vital contributing factor towards successful EHRS implementation (Adler, 2007;Carayon et al, 2009;Lorenzi et al, 2009). While some research has suggested that the formulation of an EHRS implementation project team should be the first step in the process of implementation (Adler, 2005;Sanchez et al, 2005), others have argued that the decision regarding composition of the project team is a step which should be taken only once the EHRS implementation plan has been approved (Ghazisaeidi et al, 2014). The project team are responsible for formulating a project plan, therefore the project team should be established early to ensure that all team members are involved in the early stage processes such as planning and decision-making.…”
Section: Factors Related To the Organisationmentioning
confidence: 99%
“…The project champion role is important to the successful implementation of an EHRS (Ludwick & Doucette, 2009b;Terry et al, 2008) and should be appointed in the early stages of implementation (Ghazisaeidi et al, 2014;Ross et al, 2016), especially the planning phase. The project champion's role is to act as a communication channel between project managers, project team members, and EHRS end-users (Yoon-Flannery et al, 2008), as well as the vendors of the technologies (Adams andCulp, 2005, Miller et al, 2003).…”
Section: The Involvement Of Champions In the Implementation Processmentioning
confidence: 99%
See 3 more Smart Citations